Romania's 1866 Electoral System and the Quest for National Sovereignty - Roghină, Răzvan Cosmin (Journal of Legal Studies, 2023)
In 1866, religion played a significant role in unifying the Romanian national spirit. A foreign prince was brought to rule under the Orthodox faith, and this religious aspect was incorporated into Article 82 of the Constitution.The limitation of political rights in Romania was based on ethnic criteria, with Jews and other non-Christians excluded from full participation. The electoral system introduced a high property-based voting qualification, reflecting, to some extent, liberal principles, but effectively limiting actual participation.Thus, the Romanian Constitution of 1866 struck a delicate balance between borrowed liberal ideals and the specific cultural context of Romania. It emphasized the role of religion and property ownership in shaping political rights and identity, while also attempting to align with European constitutional standards. The electoral system of 1866 in Romania fell short of democratic ideals and perpetuated inequalities. It shaped the political landscape and had far-reaching consequences for the country's governance and representation.